1996
DOI: 10.1200/jco.1996.14.2.351
|View full text |Cite
|
Sign up to set email alerts
|

High-dose versus low-dose cisplatin in combination with cyclophosphamide and epidoxorubicin in suboptimal ovarian cancer: a randomized study of the Gruppo Oncologico Nord-Ovest.

Abstract: This study shows that doubling the dose-intensity and total dose of cisplatin in combination with epidoxorubicin and cyclophosphamide has significant toxic effects and does not improve clinical outcome in patients with suboptimal ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…Dose-intense treatment (higher mg per m 2 per unit of time) has been found to improve the survival of patients with breast cancer and other cancers (Hudis et al, 1999;Citron et al, 2003). But most clinical trials among patients with OC have failed to show a survival advantage of dose-intense regimens (McGuire et al, 1995(McGuire et al, , 1996Conte et al, 1996;Jakobsen et al, 1997;McGuire, 1997;Gore et al, 1998). For example, the Gynecologic Oncology Group (GOG) compared patients treated with eight cycles of standard dose cisplatin and cyclophosphamide to those receiving four cycles of high-dose therapy.…”
mentioning
confidence: 99%
“…Dose-intense treatment (higher mg per m 2 per unit of time) has been found to improve the survival of patients with breast cancer and other cancers (Hudis et al, 1999;Citron et al, 2003). But most clinical trials among patients with OC have failed to show a survival advantage of dose-intense regimens (McGuire et al, 1995(McGuire et al, , 1996Conte et al, 1996;Jakobsen et al, 1997;McGuire, 1997;Gore et al, 1998). For example, the Gynecologic Oncology Group (GOG) compared patients treated with eight cycles of standard dose cisplatin and cyclophosphamide to those receiving four cycles of high-dose therapy.…”
mentioning
confidence: 99%
“…In advanced ovarian cancer the dose increase of each cycle with unchanged intervals did translate to an increase in sideeffects and limitation of dose intensification (Conte et al, 1996). However, acceleration of the same drugs has been shown to be feasible (Pronzato et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing platinum salt doses led to discordant data [7][8][9]. Increasing DI and/or total dose (TD), with either CDDP or CBDCA, enhances toxicity, while the therapeutic benefit remains slight [7,[10][11][12]. Reports of CBDCA dose escalation showed that with an alkylating agent, it could be safely delivered at AUC from 5 to 7 [11].…”
Section: Discussionmentioning
confidence: 99%
“…To answer the question as to whether the higher DI, the better results in AOC, cytotoxic drugs must be found whose dose can be increased safely to obtain such DI variations. Increasing platinum salt doses led to discordant data [7][8][9]. Increasing DI and/or total dose (TD), with either CDDP or CBDCA, enhances toxicity, while the therapeutic benefit remains slight [7,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%